IPS Learning Implementation Using Outdoor Study Methods to Improve Student Activity - Ni’mah, Afifatun; Zarkasi, Zarkasi; Fatmawati, Noor (Proceeding International Conference on Religion, Science and Education, 2024)
The purpose of this research is to know: 1) Characteristics of outdoor study method on learning IPS material economic activity in class VII MTs Miftahussalam 1 Demak, 2) Implementation of outdoor studies method on the learning of IPS materials economic activity, 3) Knowing learning access implementation of outdoors study method to economic activity material. This research is field research with a qualitative descriptive approach, with data obtained from observations, interviews, documentation, as well as rafting. Subsequently, all data is collected analyzed, and concluded through data reduction, data presentation, and data verification. The results of the research obtained: 1) the characteristics in the method of outdoor study is learning outside the classroom using the canteen as an adequate school facility so that it can be a strategic location on the material of economic activities, 2) the implementation of the outdoor study activities in the learning IPS is going smoothly due to the preparation of mature in terms of the place, material and tasks that have been prepared by the teacher, with the environment around the madrasah that supports very beneficial in the process of learning using the method outdoor study, this method is used by the IPS teacher on the materials of economic activity consisting of the production of consumption and distribution, because the environment of the Madrasah besides there are also the grobak merchants carefully arranged by madrasha, so it becomes compatible with the material, in addition there is an inhibitory factor, i.e. management of time in the presentation as well as interaction of students with traders who pass the specified time limit, 3) learning access in the application of outdoor studies activities i. e. can work together well, communicate widely, have a sense of behavior well, are able to solve the problems that are observed economically, while the economic activity is expected to be understood by the highest percentage of the outdoorship of the activity, and the study is demonstrated by a high degree of the ability to understand the environment.